PERLINDUNGAN HUKUM TERHADAP ISTRI SEBAGAI KORBAN ATAS TINDAKAN KEKERASAN DALAM RUMAH TANGGA - Merita, Eni; Afriani, Kinaria (Faculty of Law, University of Palembang, 2022)
Incidents of domestic violence often occur, but not many people seem to talk about it. The house that should be a place of refuge, often becomes a dangerous place for wives and children. There are various factors behind it, among others, because our society still does not consider the issue of domestic violence as a social problem, but rather an individual issue, which should not be intervened by outside parties. that according to the Law of the Republic of Indonesia No. 23 of 2004 concerning the elimination of domestic violence, Article 16 paragraph (1) states that within twenty four hours from the time of knowing or receiving a report of domestic violence, the police must immediately provide temporary protection to the victim, while Article 16 paragraph (2) states that the temporary protection as referred to in paragraph (1) is given no later than seven days after the victim is received or handled.paling lama tujuh hari sejak korban doterima atau ditangani.